Pengaruh Return On Assets (ROA) dan Earning Per Share (EPS) terhadap Harga Saham dengan Net Profit Margin (NPM) sebagai Variabel Intervening (Perusahaan Manufaktur Subsektor Makanan dan Minuman di BEI Periode 2020–2024) - Dwi Mesa Fadillah; Elfiswandi Elfiswandi (Lembaga Yasin AlSys, 2026)
The high volatility of stock prices during the COVID-19 pandemic and the subsequent economic recovery has created a need to re-examine the reliability of profitability ratios as signals for investors, particularly in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia, BEI). This study aims to analyze the effect of Return on Assets (ROA) and Earnings Per Share (EPS) on stock prices, with Net Profit Margin (NPM) as an intervening variable, over the 2020–2024 period. A quantitative approach with an explanatory design was employed, involving 25 companies (125 observations) selected through purposive sampling. Secondary data were obtained from annual financial reports published by BEI and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and path analysis with the assistance of SPSS version 26. The results show that ROA has a positive and significant effect on NPM and stock prices, while EPS has a positive and significant effect on stock prices but does not have a significant effect on NPM. NPM does not have a significant effect on stock prices and does not mediate the relationship between either ROA or EPS and stock prices. These findings indicate that investors prioritize ROA and EPS as direct signals in assessing stocks, whereas NPM does not play a meaningful mediating role. The implications suggest that companies need to enhance the efficiency of asset utilization and earnings per share performance to strengthen investor confidence and maintain stock attractiveness amid volatile market conditions.